The threshold of rule productivity in infants - Shi, Rushen; Emond, Emeryse (Frontiers in Psychology, 2023)
Most learning theories agree that the productivity of a rule or a pattern relies on regular exemplars being dominant over exceptions; the threshold for productivity is, however, unclear; moreover, gradient productivity levels are assumed for different rules/patterns, regular or irregular. One theory (Yang, 2016), the Tolerance Principle (TP), specified a productivity threshold applicable to all rules, calculated by the numbers of total exemplars and exceptions of a rule; furthermore, rules are viewed as quantal, either productive or unproductive, with no gradient levels. We evaluated the threshold and gradience-quantalness questions by investigating infants’ generalization. In an implicit learning task, 14-month-olds heard exemplars of an artificial word-order rule and exceptions; their distributions were set closed to the TP-threshold (5.77) on both sides: 11 regular exemplars versus 5 exceptions in Condition 1 (productiveness predicted), and 10 regular exemplars versus 6 exceptions in Condition 2 (unproductiveness predicted). These predictions were pitted against those of the statistical majority threshold (50%), a common assumption which would predict generalization in both conditions (68.75%, 62.5%). Infants were tested on the trained rule with new exemplars. Results revealed generalization in Condition 1, but not in Condition 2, supporting the TP-threshold, not the statistical majority threshold. Gradience-quantalness was assessed by combined analyses of Conditions 1-2 and our previous experiments (Koulaguina & Shi, 2013, 2019). The training across the conditions contained gradually decreasing regular exemplars (100%, 80%, 68.75%, 62.5%, 50%) relative to exceptions. Results of test trials showed evidence for quantalness in infants (productive: 100%, 80%, 68.75%; unproductive: 62.5%, 50%), with no gradient levels of productivity.